Hepatitis B surface antigen reduction as a result of switching from long‐term entecavir administration to tenofovir. Issue 3 (24th October 2019) - Tamaki, Nobuharu; Kurosaki, Masayuki; Kirino, Sakura; Yamashita, Koji; Osawa, Leona; Sekiguchi, Shuhei; Hayakawa, Yuka; Wang, Wan; Okada, Mao; Higuchi, Mayu; Takaura, Kenta; Maeyashiki, Chiaki; et al.
Abstract : Background and Aim: Loss of hepatitis B surface antigen (HBsAg) is an important goal in the treatment of chronic hepatitis B. We investigated whether switching from long‐term entecavir (ETV) administration to tenofovir (TFV) (tenofovir alafenamide [TAF] or tenofovir disoproxil fumarate [TDF]) could contribute to the reduction of HBsAg levels. Methods: The degree of HBsAg reduction by 48 weeks in 30 patients following switching from ETV to TFV was compared with results from 147 patients who continued ETV as a control. Results: TFV group switched to TFV after mean 6.79 years of ETV administration. HBV‐DNA levels remained below 1.0 log IU/mL in all cases in both groups during 48 weeks. Median HBsAg reduction at 48 weeks was 0.075 (−0.05 to 0.38) log/IU/mL in the TFV switch group, and 0.070 (−0.28 to 0.50) in the ETV continuation group, which was not statistically significant ( p = 0.5). In a subgroup of hepatitis B e antigen negative patients whose HBsAg had not been reduced (HBsAg reduction ≤0 log IU/mL) in the 48 weeks prior to entry into the study, HBsAg reduction was significantly higher in the TFV switch group than in the ETV continuation group (0.15 [0.07–0.135] in TFV, 0.09 [−0.14 to 0.25] log IU/mL in ETV, p = 0.04). Conclusion: Although HBsAg reduction is equivalent with ETV continuation and switching to TFV in all patients at 48 weeks, switching from ETV to TFV could provide an alternative therapeutic strategy toward HBsAg elimination in a specific subpopulation of patients. Abstract : Hepatitis B surface antigen (HBsAg) reduction is equivalent with entecavir (ETV) continuation and switching to TFV in all patients at 48 weeks. However, a significant reduction in HBsAg was observed in a subgroup of Hepatitis B e‐antigen‐negative patients whose HBsAg was not reduced during ETV therapy. In such cases, HBsAg reduction could be expected following a switch to TFV.